2017
DOI: 10.3389/fimmu.2017.01259
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Specificity Phosphatase 12 Targets p38 MAP Kinase to Regulate Macrophage Response to Intracellular Bacterial Infection

Abstract: The mitogen-activated protein kinase (MAPK) cascades are activated in innate immune cells such as macrophages upon the detection of microbial infection, critically regulating the expression of proinflammatory cytokines and chemokines such as TNF-α, IL-6, and MCP-1. As a result, activation of MAPKs is tightly regulated to ensure appropriate and adequate immune responses. Dual-specificity phosphatases (DUSPs) are a family of proteins which specifically dephosphorylates threonine and tyrosine residues essential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…Subsequently, we investigated the mechanisms by which DUSP12 inhibits the progression of NAFLD/NASH. Considering that DUSP12 could regulate microbial infection and cardiac hypertrophy through modulating MAPK signaling, MAPK pathways are well known to regulate metabolic dysfunction and hepatic steatosis during the pathogenesis of NAFLD . Thus, we examined whether DUSP12 could regulate MAPK signaling in hepatic steatosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, we investigated the mechanisms by which DUSP12 inhibits the progression of NAFLD/NASH. Considering that DUSP12 could regulate microbial infection and cardiac hypertrophy through modulating MAPK signaling, MAPK pathways are well known to regulate metabolic dysfunction and hepatic steatosis during the pathogenesis of NAFLD . Thus, we examined whether DUSP12 could regulate MAPK signaling in hepatic steatosis.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ectopic expression of DUSP12 using a retroviral expression system induced the suppression of adipogenic differentiation and lipid accumulation . More recently, studies showed that DUSP12 could protect against microbial infection by inhibiting MAPK‐mediated expression of proinflammatory mediators such as tumor necrosis factor alpha (TNF‐α), interleukin (IL)‐1β, and monocyte chemoattractant protein 1 . Providing further support, DUSP12 deficiency apparently aggravated pressure overload–induced cardiac hypertrophy and fibrosis by inhibiting activation of JUN N‐terminal kinase (JNK) .…”
mentioning
confidence: 99%
“…DUSP7, DUSP12, DUSP13B, and DUSP18 have also been analyzed as dephosphorylating and inactivating regulators of JNK [73,83,95,114]. When DUSP12 was overexpressed in RAW264.7 cells that were stimulated with LPS, the level of p-JNK was significantly reduced over time compared with control cells [114].…”
Section: Negative Regulation Of Jnk By Duspsmentioning
confidence: 99%
“…In the left-pathway in the early-stage CRC cells, the ligand PTK6 binds to the receptor STAP2 phosphorylated in the hypoxic microenvironment (Semenza, 2016). While STAP2 is modified by phosphorylation, the signal is transmitted to cascade proteins TUBB1, armadillo repeat containing 8 (ARMC8), and MAP4K1 (Fujita et al, 2014;Cho et al, 2017). At this point, with signal coupling from SIM1, the pathway activates the MAPK signaling pathway which is related to the control of immune response.…”
Section: Genetic and Epigenetic Progression Mechanisms Of Early-stagementioning
confidence: 99%
“…Based on the investigation of the core genetic and epigenetic network, we identified some pathogenic biomarkers for the design of multiple drugs against CRC. In early-stage disease, PTK6 (hypoxic environment) binds with STAP2 to activate essential protein MAP4K1 and consequently the MAPK pathway (Fujita et al, 2014;Cho et al, 2017). WIF1 (Signal transduction) binds with WNT4 to activate the WNT signaling pathway (Seth and Ruiz I Altaba, 2016;Tang et al, 2018).…”
Section: Genetic and Epigenetic Carcinogenic Mechanisms In Early-stagmentioning
confidence: 99%